EFEK MODEL PEMBELAJARAN KOOPERATIF TIPE MURDER BERBASIS MIND MAPPING TERHADAP PRESTASI DAN KREATIVITAS - Dakusta Puspitasari (STAI Syubbanul Wathon Magelang, 2017)
This study aims to find out which learning model produces better mathematics learning achievement and creativity, students who are subject to mind mapping-based MURDER learning models or MURDER learning models (M). The population in this study were eighth-grade students of State Middle Schools in Magelang District. Sampling is done by stratified cluster random sampling technique. Data collection techniques using the questionnaire method learning achievement tests. Testing the hypothesis in this study uses a two-way MANOVA analysis with unequal cells. The results showed that first, students with mind mapping-based MURDER learning models produced achievements that were as effective as students with MURDER learning models, and students with mind mapping-based MURDER learning models produced better creativity than students with MURDER learning models.